Catalpol Ameliorates Podocyte Injury by Stabilizing Cytoskeleton and Enhancing Autophagy in Diabetic Nephropathy - Yan Chen; Qingpu Liu; Zengfu Shan; Wangyang Mi; Yingying Zhao; Meng Li; Baiyan Wang; Xiaoke Zheng; Xiaoke Zheng; Weisheng Feng; Weisheng Feng (Frontiers Media S.A., 2019)
Catalpol, an iridoid glycoside extracted from Rehmannia glutinosa, has been found to ameliorate diabetic nephropathy (DN), but the mechanism has not been clarified. Podocyte injury play a key role in the pathogenesis of DN. This study mainly investigated the protective effect and potential mechanism of catalpol on podocyte injury of DN in vivo and in vitro. The results indicated that the pathological features of DN in mice were markedly ameliorated after treatment with catalpol. Moreover, podocyte foot process effacement, and down-regulation of nephrin and synaptopodin expression in DN mice were also significantly improved after treatment with catalpol. In vitro, catalpol rescued disrupted cytoskeleton and increased migration ratio in podocytes induced by high glucose, the effect might be attributable to the inhibition of RhoA and Cdc42 activities but not Rac1. Furthermore, the impaired podocyte autophagy in DN mice was significantly enhanced after catalpol treatment. And catalpol also enhanced autophagy and lysosome biogenesis in cultured podocytes under high glucose condition. In addition, we found that catalpol could inhibit mTOR activity and promote TFEB nuclear translocation in vivo and in vitro experiments. Our study demonstrated that catalpol could ameliorate podocyte injury in DN, and the protective effect of catalpol might be attributed to the stabilization of podocyte cytoskeleton and the improvement of impaired podocyte autophagy.